Comparison between forward and backward gait retraining for mobility in individuals with mild to moderate Parkinson’s disease - Grobbelaar, Roné (Stellenbosch : Stellenbosch University, 2017)
Thesis (MScSportSc)--Stellenbosch University, 2017